The influence of degree of loading and load placing on steerability of vehicles - Ihor Kuzio; Mariia Sokil (Transport Technologies, 2021)
The methodology of research of the influence of the degree of loading, kinematic parameters of movement, and nonlinear power characteristics of elastic elements and shock-absorbers of the suspension system on their steerability on curved sections of the road is developed. The research is based on the equation of kinetostatics of the system of sprung-unsprung part and differential equations that relate the motion of the sprung part of vehicles. Concerning the last, they take into account both loading of a vehicle and nonlinear-elastic characteristics of shock-absorbers. For the case when elastic characteristics of shock-absorbers are described by degree or close to it dependence, the fluctuation of sprung part is described analytically. Their peculiarity is that the frequency and therefore dynamic force of wheels pressure on the bearing surface (road) depends on the amplitude. It is the last value and characteristics of the road surface that determine the main parameters of steerability and stability of the movement of wheeled vehicles along curved sections of the road. Taken together, the mentioned above allowed to obtain the dependence of the critical value of the dynamic angle of rotation of the steered wheels, as a function of the amplitude of longitudinal-angular oscillations, kinematic motion parameters, and the level of loading of a vehicle. It is established: